2023
DOI: 10.1037/dev0001420
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver faces capture 6- to 10-year-old children’s attention during an online visual search task.

Abstract: Developing attention skills allow children to parse their complex world by orienting to a subset of especially salient or meaningful inputs. Infants and children are biased to orient to faces and have difficulty ignoring faces when they appear as distractors. Although these past findings suggest that faces are more salient than nonsocial stimuli, it is unclear whether specific types of faces capture attention to a greater extent than others. Caregiver faces are one of the most prevalent and socially motivating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…During some trials, either their own caregiver's face or a stranger's face appeared as one of the distractors. Children demonstrated poorer target detection performance when their caregiver's face appeared, suggesting that they were biased to orient to their caregiver's face even though it was irrelevant to the ongoing task (Hunter & Markant, 2023b). Together, these studies indicate that by 4 years of age children are biased to detect caregiver faces in complex arrays containing competing visual information.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…During some trials, either their own caregiver's face or a stranger's face appeared as one of the distractors. Children demonstrated poorer target detection performance when their caregiver's face appeared, suggesting that they were biased to orient to their caregiver's face even though it was irrelevant to the ongoing task (Hunter & Markant, 2023b). Together, these studies indicate that by 4 years of age children are biased to detect caregiver faces in complex arrays containing competing visual information.…”
mentioning
confidence: 82%
“…Children detected their own caregiver's face within the array of competing faces faster than they detected a stranger face, indicating biased orienting to caregivers. Hunter and Markant (2023b) similarly found that 6-to 10-year-old children were more distracted by their caregiver's face during an attention capture task. Children searched for a target object within arrays that contained a varying number of distractors.…”
mentioning
confidence: 82%
See 3 more Smart Citations